2021
DOI: 10.2196/23487
|View full text |Cite|
|
Sign up to set email alerts
|

A Direct-to-Public Peer Support Program (Big White Wall) Versus Web-Based Information to Aid the Self-management of Depression and Anxiety: Results and Challenges of an Automated Randomized Controlled Trial

Abstract: Background Effective help for depression and anxiety reaches a small proportion of people who might benefit from it. The scale of the problem suggests the need for effective, safe web-based public health services delivered directly to the public. One model, the Big White Wall (BWW), offers peer support at low cost. As these interventions are delivered digitally, we tested whether a randomized controlled trial (RCT) intervention could also be fully delivered and evaluated digitally. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…We used only one questionnaire each for assessing depression and anxiety symptom severity. This decision was made keeping in mind that filling long questionnaires online is not a pleasant experience for the users and might increase dropout (Morriss et al, 2021). Also, while including multiple questionnaires for assessing the same disorder might improve validity, it also increases the risk of getting false-positive results by chance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used only one questionnaire each for assessing depression and anxiety symptom severity. This decision was made keeping in mind that filling long questionnaires online is not a pleasant experience for the users and might increase dropout (Morriss et al, 2021). Also, while including multiple questionnaires for assessing the same disorder might improve validity, it also increases the risk of getting false-positive results by chance.…”
Section: Discussionmentioning
confidence: 99%
“…In a fully remote trial of an app-based intervention, Arean et al (Arean et al, 2016) reported that 57.9% of the participants did not even download their assigned apps. Similarly, in another study involving no human contact, Morriss et al (Morriss et al, 2021) reported that only 57.3% of participants randomized to the experimental group signed up for the intervention and only 42.5% accessed it more than once. Morriss et al (Morriss et al, 2021) further reported an attrition rate of 84.9% at 3-week follow-up with the attrition rate increasing at later follow-up points.…”
Section: Adherence Rates In Ccbt Interventionsmentioning
confidence: 93%
See 2 more Smart Citations
“…There were mostly contextual issues noted in recent studies. An automated randomized controlled trial of an online peer-support program (Big White Wall) versus web-based information for self-management of anxiety and depression suggested a personal approach for participant engagement to explain the benefits of this novel intervention [33]. It was proposed that user engagement and satisfaction with a digital platform (Thought Spot) be related to content relevance, ease of learning, and available features [34].…”
Section: Systemic and Practical Issuesmentioning
confidence: 99%